Analysis of Potential Community-based Camping Attraction in Gambung Village, Mekarsari - Sherly Raka Siwi Putri Utomo (Politeknik Negeri Bandung, 2021)
The tourist village of Gambung Mekarsari is one of ten tourist villages established by the Bandung Regency government in 2016. This village has a lot of tourism potential, one of them is the Sahyang Bodas camping ground area managed by the community. Community-based tourism have been the driving force of tourism development in the region for years. However, it has not yet been optimally developed. This study aims to analyze the potential of tourist attractions in the area and find solutions to problems that can later be used as references to determine strategies for developing potential and tourist attractions at the Sahyang Bodas camping ground, Gambung Village, Mekarsari. The components that will be analyzed are related to the 4A tourism components, including Attraction, Accommodation, Accessibility, and Ancillary. This study uses a qualitative approach and SWOT analysis with data collection carried out through Focus Group Discussions, direct observations in the field, and in-depth interviews. Based on the review and analysis carried out regarding the potential and problems in the field, the results obtained that the potential attraction in the camping ground area of ​​Gambung Mekarsari Village has enormous potential to be developed.